2021
DOI: 10.18632/aging.203025
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA ABCB10 contributes to laryngeal squamous cell carcinoma (LSCC) progression by modulating the miR-588/CXCR4 axis

Abstract: Laryngeal squamous cell carcinoma (LSCC) is a common head and neck cancer with a high metastasis and poor prognosis. Circular RNAs (circRNAs) are a type of non-coding RNAs (ncRNAs) with regulatory function and broadly participate in cancer development. However, the correlation of circular RNA ABCB10 (circABCB10) with LSCC remains unclear. Here, we were interested in the role of circABCB10 in the modulation of LSCC progression. Our data demonstrated that the depletion of circABCB10 significantly inhibited the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…circ_0067934 is an oncogene promoting LSCC and may be a viable prognostic biomarker and target for diagnosis and treatment ( 28 ). Zhao et al ( 29 ) reported that circ ATP binding cassette subfamily B member 10 promotes LSCC progression and may act as a possible target in LSCC therapy. In addition, circRNA_103862 promotes LSCC proliferation by targeting the miR-493-5p/golgi membrane protein 1 axis and might serve as a potential prognosis marker and therapy target for LSCC ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…circ_0067934 is an oncogene promoting LSCC and may be a viable prognostic biomarker and target for diagnosis and treatment ( 28 ). Zhao et al ( 29 ) reported that circ ATP binding cassette subfamily B member 10 promotes LSCC progression and may act as a possible target in LSCC therapy. In addition, circRNA_103862 promotes LSCC proliferation by targeting the miR-493-5p/golgi membrane protein 1 axis and might serve as a potential prognosis marker and therapy target for LSCC ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs have shown great potential as therapeutic molecular tools in many cancers such as HNSCC ( 110 , 166 , 167 ), breast cancer ( 168 ), hepatocellular carcinoma ( 169 ), papillary thyroid cancer ( 170 ) gastric cancer ( 171 ). Compared with existing linear miRNA antagonists, circRNAs are structurally more stable, more resistant to degradation by nucleases without chemical modification, and well tolerated in vivo ( 172 ).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of circRNAs have been uncovered to be involved in the development of LSCC, 26 , 27 , 28 and we studied the function of circBFAR in LSCC. Guo et al 29 found that circBFAR was upregulated as an oncogene in patients with pancreatic ductal adenocarcinoma (PDAC), which was pertinent to tumor node metastasis and poor prognosis of PDAC patients.…”
Section: Discussionmentioning
confidence: 99%